Effect of interactive cognitive-motor training on eye-hand coordination and cognitive function in older adults - Chan, Pi-Tuan; Chang, Wen-Chi; Chiu, Huei-Ling; Kao, Ching-Chiu; Liu, Doresses; Chu, Hsin; Chou, Kuei-Ru (BMC geriatrics, 2019)
Poor eye-hand coordination is associated with the symptoms of the early stage of cognitive decline. However, previous research on the eye-hand coordination of older adults without cognitive impairment is scant. Therefore, this study examined the effects of interactive cognitive-motor training on the visual-motor integration, visual perception, and motor coordination sub-abilities of the eye-hand coordination and cognitive function in older adults. A double-blind randomized controlled trial was conducted with older adults. Sixty-two older adults were randomly assigned to the experimental (interactive cognitive-motor training) or active control (passive information activity) group, and both groups received 30 min of training each week, three times a week for 8 weeks. The primary outcome was eye-hand coordination, which was further divided into the sub-abilities of visual-motor integration, visual perception, and motor coordination. The secondary outcome was cognitive function. The generalized estimating equation was used to examine differences in immediate posttest, 3-month posttest, and 6-month posttest results between the two groups. Additionally, the baseline effect sizes were compared with the effect sizes of the immediate posttest, 3-month posttest, and 6-month posttests for the experimental group. There were no statistically significant differences between the intervention and control groups. The only statistically significant difference between the groups was in the attention dimension of cognitive function (p = 0.04). The visual-motor integration results showed a small to moderate effect size for pre post comparisons. The 24 sessions of interactive cognitive-motor training showed no difference to an active control intervention. In the future, this intervention could be further investigated to establish whether it can be superior to an active control group in other populations. The study protocol has been published on Chinese Clinical Trial Registry (ChiCTR) (registry no.: ChiCTR-IOR-14005490 ).